2021
DOI: 10.1507/endocrj.ej20-0541
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermography in the diagnostic investigation of thyroid nodules

Abstract: Thyroid nodules (TN) are common in the general population, and the clinical importance of diagnosing thyroid nodules is based on excluding the possibility of thyroid cancer, which occurs in 7-15% of cases. The thyroid gland, owing to its superficial location, is easily accessible via thermography, a noninvasive method of recording body temperature that measures infrared radiation emitted by the body surface. Therefore, this study aimed to evaluate the temperature differences between benign and malignant TN by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
2
Order By: Relevance
“…33,34 Thermography has already been included in the evaluation of vascular pathologies. In a study of thermography for thyroid nodules, Damião et al 35 found that malignant nodules have higher temperatures than their benign counterparts (33.46 °C vs. 33.01 °C). In a paper by Cruz Segura et al, 16 the usefulness of thermography was demonstrated given that the temperature obtained from obstructed vessels after microsurgical reconstruction with flaps was 31.95 °C on average, in comparison with 34.80 °C in unobstructed vessels.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Thermography has already been included in the evaluation of vascular pathologies. In a study of thermography for thyroid nodules, Damião et al 35 found that malignant nodules have higher temperatures than their benign counterparts (33.46 °C vs. 33.01 °C). In a paper by Cruz Segura et al, 16 the usefulness of thermography was demonstrated given that the temperature obtained from obstructed vessels after microsurgical reconstruction with flaps was 31.95 °C on average, in comparison with 34.80 °C in unobstructed vessels.…”
Section: Discussionmentioning
confidence: 99%
“… 29–31 It is used to diagnose pneumonia and also supports diagnosing thyroid diseases. 32 In cardiology, it can be used to monitor the circulation or heart during cardiac surgery, while in allergology, it supports diagnosing respiratory and food allergies. 33–35 It was also found that a thermal imaging analysis can be an effective tool for diagnosing peripheral vascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the use of IRT in biomedicine is that changes in body temperature may be indicative of the existence of disease conditions. Such temperature changes are related to the inflammation produced by the disease, and can be detected and recorded with a thermographic camera [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Thermal (infrared) imaging offers a number of advantages: it is noninvasive, involves no physical contact with the measured surface, and affords images that can be filed and processed to evaluate neurological disorders (e.g., spinal cord and peripheral nerve damage), vascular diseases (e.g., Raynaud’s disease) and bone and joint disorders (e.g., myofascial pain syndrome, rheumatoid arthritis and sports injuries).…”
Section: Introductionmentioning
confidence: 99%